Increasing performance of chiller systems in high-rise buildings by load optimization - Arifin, Zainal; Fachruroji, Fachruroji; Huda, Muhammad (Institute of Advanced Engineering and Science, 2024)
Recently, the construction of high-rise buildings has been increasing significantly along with economic growth. Therefore, electricity is also going up due to the energy demand of the building. The air conditioning system is the enormous energy consumption in high buildings. The green building concept has been introduced regarding the energy efficiency of a high-rise building. This study investigated the energy consumption in a high building (47 floors) using the load optimization method for the chiller system. The load optimization was conducted by configuring five chillers systems consisting of integral compressors, cooling towers, and pumps. This study obtained the decreasing energy consumption by the chiller's operation load sequencing based on 24-hour data optimization. Optimized chiller performance satisfied the green building standards. However, load optimization on high buildings is highly recommended as an effective way to achieve green building status. Further research is recommended for implementing such optimization at other facilities, such as industrial plants, hospitals, airports, and manufacturing plants.